Effect of spacing, concentration of NaCl solution, and biasing of graphite electrodes towards conductometric sensor response - Izzah Wadhihah Zulkarnain; Wan Fazlida Hanim Abdullah; Ili Shairah Abdul Halim; Muhammad Izzat Alif Muslan (Institute of Advanced Engineering and Science, 2024)
An electrical conductivity (EC) sensor is a conductometric sensor used to measure a solution's ability to transmit electrical charges. However, EC sensing accuracy and stability are not consistent due to many factors, such as gap spacing between electrodes, concentration of the solution, and electrical biassing. This study investigates the influence of the gap spacing between electrodes, the concentration of the solution, frequency, and voltage input applied to the EC sensor electrode on EC sensor measurement and provides insights into the relationship between these parameters and the sensor's performance using the voltage divider rule which is the simpler way to measure the conductivity of the solution. From this investigation, gap spacing between the electrodes, the concentration of the solution, frequency below 50 Hz, and voltage input have been found to directly affect the EC sensor measurement. However, there is no significant change in EC sensor measurement regarding the frequency applied to graphite electrodes when the frequency is above 50 Hz. The findings of this study highlight the complex interplay between the physical setup parameters and EC sensor measurement.